2023
DOI: 10.1111/1750-3841.16596
|View full text |Cite
|
Sign up to set email alerts
|

Gametophyte phase of commercial kelps, the potential food supplements for essential fatty acids and n‐3 polyunsaturated fatty acids

Abstract: For heteromorphic algae with alternating generations, the thallus and gametophyte phases are different morphologies in free-living life history.The thalli are popular used as traditional vegetables and herbal drugs, whereas the gametophyte phases are little involved. To better understand the functional lipids in the gametophyte phase of three commercial kelps, Saccharina japonica, Undaria pinnatifida, and Costaria costata, the contents of total lipids (TLs), fatty acid (FA) profiles, and transcriptomic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…This species is characterized by its high protein content and dietary fiber, as well as significant amounts of calcium, sodium, potassium, iron, magnesium, vitamin B, vitamin A, and antioxidants. 19 U. pinnatifida is well known for containing phenolic compounds 20 with antioxidant, 21 anti-inflammatory, 22 antidiabetic, 23 and antibacterial 24 activities. Furthermore, our quantitative analysis showed that galactans was the most abundant compound in U. pinnatifida.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is characterized by its high protein content and dietary fiber, as well as significant amounts of calcium, sodium, potassium, iron, magnesium, vitamin B, vitamin A, and antioxidants. 19 U. pinnatifida is well known for containing phenolic compounds 20 with antioxidant, 21 anti-inflammatory, 22 antidiabetic, 23 and antibacterial 24 activities. Furthermore, our quantitative analysis showed that galactans was the most abundant compound in U. pinnatifida.…”
Section: Introductionmentioning
confidence: 99%
“…U. pinnatifida stands out as a notable reservoir of many essential nutrients. This species is characterized by its high protein content and dietary fiber, as well as significant amounts of calcium, sodium, potassium, iron, magnesium, vitamin B, vitamin A, and antioxidants 19 . U. pinnatifida is well known for containing phenolic compounds 20 with antioxidant, 21 anti‐inflammatory, 22 antidiabetic, 23 and antibacterial 24 activities.…”
Section: Introductionmentioning
confidence: 99%